Efektivitas Pemanfaatan Google Form dalam Asesmen PAI di SMK Satria - Fathur Rohman Romadhon; Lismawati Lismawati (Departement of Mathematics Education, 2024)
In several schools, for the evaluation midterm test and final test used google form. This research is aimed to know the effectiveness of using google form as medium for Islamic education assessment in SMK SATRIA. This research is used descriptive qualitative method at SMK SATRIA , Srengseng, Kembangan, Jakarta. This research is done among October to November 2023. The Data Collective is used observation, interview, and documentation. The interview is participated by the principal, class teachers, lesson teachers, students and the parents of students. Some of teacher and management school said the use of google form was effective in Islamic education assessment for students. Besides that, for students, the use of google form was giving the ease to know the result of assessment directly after they fill and submitted the answers of assessment, so the students did not wait the result from the teachers based on the criteria of midterm and final test. The teachers and students gave positive responses to the use of google form as medium for Islamic education assessment in SMK SATRIA, Jakarta. Through this research, can be showed that google form was effective to use , based on the effectiveness of time, budget, human, and ease to use.